Synthesis and analysis of temporal fault trees with PANDORA: the time of Priority AND gates - Walker, Martin; Papadopoulos, Yiannis (Nonlinear Analysis: Hybrid Systems, 2008)
Classical Fault Tree Analysis (FTA) can determine the effects of combinations of failure events on a system but cannot capture the significance of the temporal order of events, which may be critical. In this paper, we propose an extension based on formal definition and use of Priority AND gates that enables representation of event sequences and analysis of temporal relationships in FTA. In addition, we show how this type of temporal analysis can be used in conjunction with a recently proposed method for automated fault tree synthesis to allow accurate failure analyses of system models to be carried out efficiently. The approach is demonstrated on a generic system with a shared backup component. The paper tentatively concludes that this type of temporal FTA can provide a more precise and ultimately more correct insight into the failure behaviour of a system.
Batch 005. Output ID 37255.
Keywords: Safety analysis; Reliability analysis; Fault tree synthesis; Temporal fault trees; Temporal logic; HiP-HOPS